Optimasi formula dan karakterisasi dodol buah salak dengan tepung singkong termodifikasi sebagai bahan pengisi - Santi Dwi Astuti; Indah Nuraeni; Bela Iji Pamungkas; Nur Wijayanti; Warsono El Kiyat (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Snake fruit is generally consumed in the form of fresh fruit, but if it is left too ripe, cracked skin can be seen, making it less attractive. Alternative processing of salak fruit is to process it into salak lunkhead. Dodol is generally produced using glutinous rice flour. In this study, another alternative was found, namely the use of modified cassava flour as a substitute for glutinous rice flour. This study used a response surface method with an experimental design using CCD (Central Composite Design) with two factors, namely salak puree and modified cassava flour. The results of this study were the optimum dodol salak formula with the highest desirability value of 0.663 in the 15.73 % salak fruit formula and 11.3 5% modified cassava flour. The results of the sensory test for salak dodol show that an increase in the proportion of pure zalacca fruit causes an increase in the flavor response of the salak and causes a decrease in response to chewiness, stickiness, hardness, white color and preferences. The increase in the proportion of modified cassava flour causes an increase in chewiness, stickiness, hardness, white color, and liking. It causes a decrease in response to the salak flavor. The average chemical test results, the optimum product has a higher difference in value for water content, namely 7.15 %, ash content 0.42 %, protein content 0.28 %, fat content 2.02 %, and energy 8.4 % than with control products. Meanwhile, carbohydrate content has a lower value difference of 2.73 % compared to the control product.